Pengaruh Iklim Sekolah dan Motivasi Kerja terhadap Kinerja Guru Sekolah Dasar Guang Ming Se-Indonesia - Rudy Sumanto; Ida Ayu Gede Yadnyawati; Muljadi Muljadi; Isomudin Isomudin (Dhammavicaya : Jurnal Pengkajian Dhamma, 2024)
The purpose of this study was to test and analyze the effect of school climate and work motivation on the performance of Guang Ming Elementary School teachers throughout Indonesia. This study uses multiple regression analysis to determine the effect of school climate and work motivation on teacher performance. The Population in this study amounted to 102 guang ming school teachers throughuot Indonesia. In this study the determination of the sample using the census method with the number of samples used in this study as many as 102 respondents. This study uses primary data, data is collected by distributing questionnaires to respondents via google forms. Testing the research hypothesis using SPSS 20.0 for Windows. The results showed that school climate had a positive effect on teacher performance at Guang Ming Elementary Schools throughout Indonesia with a correlation coefficient score of ry1 = 0.471 and a determination coefficient score of r2y1 =0.222. Work motivation has a positive effect on teacher performance Guang Ming Elementary Schools in Indonesia with a correlation coefficient score of ry2 = 0.526 and a determination coefficient score of r2y2 = 0.276. School climate and work motivation have a positive and significant effect on the performance of teachers at Guang Ming Elementary Schools in Indonesia with a correlation coefficient score of ry1.2 = 0.627 and a coefficient of determination score of r2y1.2 = 0.393. The regression equation in this study is as follows: Ŷ = 45,665 + 0.266X1 + 0.385X2. Based on these results, to optimize teacher performance, policies and regulations are needed to improve school climate and work motivation.